2003
DOI: 10.1007/s00113-003-0690-x
|View full text |Cite
|
Sign up to set email alerts
|

Patellektomie nach Trauma?beeinflusst der Zeitpunkt das Ergebnis?

Abstract: Primary reconstruction of the patella is recommended in multifragmentary fractures; if the outcome is poor, however, patellectomy should be considered early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…In 1909 Heideck reviewed 1,100 patellar fractures and stated that total patellectomy should be considered on a case-by-case basis only as a last resort if the patella is not salvageable [ 34 ]. Several subsequent studies confirmed this finding and concluded that the clinical results after patellectomy are devastating [ 59 ], [ 82 ]. Kaufer et al reported that an increase of quadriceps muscle force of up to 30% is necessary in order to sufficiently extend the knee after patellectomy.…”
Section: Operative Treatmentmentioning
confidence: 77%
“…In 1909 Heideck reviewed 1,100 patellar fractures and stated that total patellectomy should be considered on a case-by-case basis only as a last resort if the patella is not salvageable [ 34 ]. Several subsequent studies confirmed this finding and concluded that the clinical results after patellectomy are devastating [ 59 ], [ 82 ]. Kaufer et al reported that an increase of quadriceps muscle force of up to 30% is necessary in order to sufficiently extend the knee after patellectomy.…”
Section: Operative Treatmentmentioning
confidence: 77%
“…Другие исследователи (E.J. Müller et al 2003) считают, что по возможности лучше сохранить целостность надколенника для восстановления функции разгибательного аппарата коленного сустава [2,13]. Brooke (1937) пришел к выводу, что у человека надколенник «не выполняет никакой полезной функции» и что колено обходится лучше без него как в отношении скорости движения, так и в силе.…”
unclassified